RIM, Munc13, and Rab3A interplay in acrosomal exocytosis - Bello, Oscar Daniel (2012)
Exocytosis is a highly regulated, multistage process consisting of multiple functionally definable stages, including recruitment, targeting, tethering, priming, and docking of secretory vesicles with the plasma membrane, followed by calcium-triggered membrane fusion. The acrosome reaction of spermatozoa is a complex, calcium-dependent regulated exocytosis. Fusion at multiple sites between the outer acrosomal membrane and the cell membrane causes the release of the acrosomal contents and the loss of the membranes surrounding the acrosome. Not much is known about the molecules that mediate membrane docking in this particular fusion model. In neurons, the formation of the ternary RIM/Munc13/Rab3A complex has been suggested as a critical component of synaptic vesicles docking. Previously, we demonstrated that Rab3A localizes to the acrosomal region in human sperm, stimulates acrosomal exocytosis, and participates in an early stage during membrane fusion. Here, we report that RIM and Munc13 are also present in human sperm and localize to the acrosomal region. Like Rab3A, RIM and Munc13 participate in a prefusion step before the efflux of intra-acrosomal calcium. By means of a functional assay using antibodies and recombinant proteins, we show that RIM, Munc13 and Rab3A interplay during acrosomal exocytosis. Finally, we report by electron transmission microscopy that sequestering RIM and Rab3A alters the docking of the acrosomal membrane to the plasma membrane during calcium-activated acrosomal exocytosis. Our results suggest that the RIM/Munc13/Rab3 A complex participates in acrosomal exocytosis and that RIM and Rab3A have central roles in membrane docking.